2012
DOI: 10.1094/pdis-03-12-0291-fe
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Effort to Fight an Enemy of Wheat and Barley: Fusarium Head Blight

Abstract: Wheat and barley are critical food and feed crops around the world. Wheat is grown on more land area worldwide than any other crop. In the United States, production of wheat and barley contributes to domestic food and feed use, and contributes to the export market and balance of trade. Fifteen years ago, Plant Disease published a feature article titled “Scab of wheat and barley: A re-emerging disease of devastating impact”. That article described the series of severe Fusarium head blight (FHB) epidemics that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
518
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 658 publications
(533 citation statements)
references
References 49 publications
7
518
2
6
Order By: Relevance
“…Both initial infection (Anderson 1948;McMullen et al 2012) and FHB development (Xu 2003;Kriss et al 2010) are favoured by warm/moist conditions, and thus the increased DON accumulation with warm and wet/ moist conditions found in our study are as expected.…”
Section: Association Between Don Content and Weather Conditions At DIsupporting
confidence: 87%
“…Both initial infection (Anderson 1948;McMullen et al 2012) and FHB development (Xu 2003;Kriss et al 2010) are favoured by warm/moist conditions, and thus the increased DON accumulation with warm and wet/ moist conditions found in our study are as expected.…”
Section: Association Between Don Content and Weather Conditions At DIsupporting
confidence: 87%
“…SPOLTI et al (2012a) , evidenciando que as populações produzem ambas as micotoxinas. Para o manejo da giberela e das micotoxinas nos grãos, é recomendado o uso de cultivares com maior grau de resistência, aplicação de fungicidas e o ajuste dos mecanismos da colheita mecânica para a eliminação de grãos giberelados (McMULLEN et al, 2012). Fungicidas do grupo dos triazóis, que possuem ação fungistática sobre F. graminearum sensu lato, têm sido indicados para uso durante o fl orescimento pleno (YIN et al, 2009).…”
Section: Introductionunclassified
“…Major FHB epidemics have occurred somewhere in the United States in every decade since the disease was formally described by W. G. Smith in 1884 (60) although, in any given location, epidemics tend to occur sporadically. During the last two decades, U.S. wheat experienced large direct production losses because of FHB (35,36) and even larger indirect losses in other sectors of the economy (43), contributing to the characterization of FHB as a reemerging disease of importance (36,53). Increased corn (Zea mays) production in wheat-growing regions, concurrent with wider adoption of reduced tillage for soil conservation, were likely contributory factors to severe epidemics beginning in the latter part of the 19th century (36,60), as pathogen survival in corn residue is an acknowledged FHB risk factor (13,27).…”
mentioning
confidence: 99%
“…FHB epidemiological research includes (i) basic documentation of epidemics and observed weather conditions at the time, a mainly descriptive effort, followed by quantification of optimal (usually controlled) conditions for various epidemiologically relevant processes (7,14,45,59,62,63); (ii) synthesis of basic epidemiological results into generalized, qualitative risk algorithms predicting FHB epidemics (47,59,63); and (iii) translation of the generalized risk algorithms into quantitative risk models (10,12,18,25,32,34,39,41,58), several of which were reviewed elsewhere (55). Within the United States, models originally developed by De Wolf and colleagues (12) and subsequently refined (39,40) are the central risk algorithms behind the Fusarium Head Blight Risk Assessment Tool (http://www.wheatscab.psu.edu), a publicly funded service providing local-level, empirical FHB predictions across 31 states (35). The models are simple, in that they contain a few easily calculated predictors, an asset when deploying models at the regional scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation